Pemberdayaan kader dalam edukasi dampak merokok terhadap kesehatan gigi dan mulut pada penderita diabetes - Nuraskin, Cut Aja; Rasidah, Rasidah; Reca, Reca; Salfiyadi, Teuku (Politeknik Kesehatan Kemenkes Aceh, 2025)
The community service activity entitled “Empowering Health Cadres in Disseminating the Impact of Smoking on Oral Health among Diabetes Mellitus Patients in Darul Imarah Subdistrict, Aceh Besar” was successfully carried out. The objective was to increase community awareness regarding the causes, symptoms, and complications of diabetes mellitus; the impact of smoking on oral health in diabetes patients; the prevention and treatment of periodontal disease; and efforts to reduce the prevalence of diabetes mellitus. The method used was education and counseling involving 40 participants, including health cadres, PKK members, youth groups, and diabetes patients.Pre-test results indicated low levels of knowledge: 55% on diabetes mellitus, 50% on the impact of smoking, 48% on periodontal disease prevention, and 52% on efforts to reduce diabetes prevalence. After the intervention, post-test results showed improvement, with knowledge increasing to 85% on diabetes mellitus, 82% on smoking impact, 80% on periodontal disease prevention, and 83% on diabetes prevention efforts. Overall, the average increase reached 31,25%. Based on the distribution of knowledge improvement, 65% of participants experienced a high increase (>30%), 30% moderate (15–30%), and 5% low (<15%). It can be concluded, Education and counseling significantly improved participants’ knowledge, with an average increase of 31,25%. The majority (65%) achieved a high level of improvement. Further guidance is recommended for participants with low improvement.